2012
DOI: 10.1242/jcs.096644
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis supports a core role forDrosophilaα-Catenin in adherens junction function

Abstract: Summary a-catenin associates the cadherin-catenin complex with the actin cytoskeleton. a-catenin binds to b-catenin, which links it to the cadherin cytoplasmic tail, and F-actin, but also to a multitude of actin-associated proteins. These interactions suggest a highly complex cadherin-actin interface. Moreover, mammalian aE-catenin has been implicated in a cadherin-independent cytoplasmic function in Arp2/3-dependent actin regulation, and in cell signaling. The function and regulation of individual molecular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 85 publications
(101 reference statements)
6
123
0
Order By: Relevance
“…A network of transcription factors, including Jing, SIX4, Yan, Similar (also known as HIF1a), Hindsight (HNT), and Jun-related antigen, is activated and controls the levels of DE-cadherin during border cell delamination and migration (Montell et al 2012). Levels of DE-cadherin need to be precisely regulated and deviations impair border cell migration; consequently, after initially reducing DE-cadherin levels during delamination, moving border cell clusters still maintain substantial levels of both DE-cadherin and its binding partner armadillo (b-catenin) between neighboring border cells to maintain collective migration as a cluster (Peifer 1993;Niewiadomska et al 1999;Sarpal et al 2012).…”
Section: Tissue Morphogenesis and Regenerationmentioning
confidence: 99%
“…A network of transcription factors, including Jing, SIX4, Yan, Similar (also known as HIF1a), Hindsight (HNT), and Jun-related antigen, is activated and controls the levels of DE-cadherin during border cell delamination and migration (Montell et al 2012). Levels of DE-cadherin need to be precisely regulated and deviations impair border cell migration; consequently, after initially reducing DE-cadherin levels during delamination, moving border cell clusters still maintain substantial levels of both DE-cadherin and its binding partner armadillo (b-catenin) between neighboring border cells to maintain collective migration as a cluster (Peifer 1993;Niewiadomska et al 1999;Sarpal et al 2012).…”
Section: Tissue Morphogenesis and Regenerationmentioning
confidence: 99%
“…Therefore, subsequent investigations of the structural elements determining the stability of the autoinhibited conformation focused on the central M region. The C-terminal domain is known to be required for actin anchorage and force transmission across the protein (24,26,57). In experiments, C-terminal domain deletion prevented ␣-catenin localization at the membrane (24,26,57).…”
Section: N-terminal Domain Does Not Contribute Directly To Autoinhibimentioning
confidence: 99%
“…The C-terminal domain is known to be required for actin anchorage and force transmission across the protein (24,26,57). In experiments, C-terminal domain deletion prevented ␣-catenin localization at the membrane (24,26,57). This result suggested cooperativity between the N-and C-terminal domains, but recent findings do not support this interpretation (39).…”
Section: N-terminal Domain Does Not Contribute Directly To Autoinhibimentioning
confidence: 99%
“…Their critical role in cell adhesion is underscored by pathological consequences of deletion or truncation of ␣-catenin genes in mammals, such as cancer metastasis (7), cerebellar hypoplasia (8), and arrhythmogenic cardiomyopathy (9). As well, the embryonic lethality has been reported for ␣-catenin-null flies (10). Cell biology studies revealed that ␣E-catenin is essential for organization of the apical junctional complex (AJC) (11), containing tight junction and AJ, by forming two types of AJs, punctum adherens and zonula adherens, in polarized epithelial cell monolayer (supplemental Fig.…”
mentioning
confidence: 99%